Histological evaluation of the exposure to 3,4-dichloroaniline in the estuarine mysid Mesopodopsis slabberi, under experimental conditions - Sardo, A. M. (2012)
This work presents an experimental approach to test Mesopodopsis slabberi as a potential indicator of pollution. The toxic effects of 3,4-dichloroaniline (DCA) on the histology of this estuarine mysid were studied. After an acclimation period of two days, the mysids were exposed to different sublethal 3,4-DCA concentrations (0.10, 0.30, 0.50, 0.90, 1.00, 1.10, 1.20, 1.30 and 1.40 mg/L), for a period of 48 h. Each concentration had seven replicates, and one control. After the exposure period, organisms were sacrificed and submitted to a standard histological procedure with some modifications. Histological effects were analyzed in several tissues and damages were found in organisms exposed to concentrations higher then 0.30 mg/L. Muscular tissue, cuticular lens and gonads were clearly affected by 3,4-DCA, presenting accumulations of this toxic substance and lesions on the structures.